Pengaruh Literasi Bisnis Digital dan Efikasi Diri terhadap Intensi Beriwirausaha Mahasiswa Pendidikan Ekonomi Fakultas Ekonomi Universitas Negeri Makassar - Asrib, Aman Rasyad; Rakib, Muhammad; Rahmatullah; M. Ihsan Said; Hasan, Muhammad (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2023)
The purpose of this study is to reveal how literacy in digital business and self-efficacy in entrepreneurial intentions in the online field of Economic Education students, Faculty of Economics, Makassar State University. By examining the relationship between variables, namely the extent to which variations in one variable will be related to other variables, is a correlation research method carried out in this study. A total of 294 students became the population and 59 students as research samples in the Economic Education study program of Makassar State University. Questionnaires and data analysis techniques are data acquisition techniques that are applied by applying descriptive statistical analysis and multiple linear regression. Hail from this study revealed that there is a positive and significant influence between Digital Business Literacy and Self-Efficacy on the Entrepreneurial Intentions of Economic Education students, Faculty of Economics, Makassar State University partially and simultaneously.